Confronted with Bullying when You Believe in a Just World - Voss, David; Newman, Leonard S. (Frontiers in Education, 2021)
Bullying has been recognized as a phenomenon that detrimentally affects the lives of many, and researchers continue to explore its various influences and correlates. We examined the relationship between the global belief in a just world (BJW; a person’s tendency to believe that life is fair and people get what they deserve) and reactions to bullying. Although BJW is undergirded by a justice motive (Dalbert, 2001), and although previous research found that global BJW is associated with more negative explicit attitudes toward bullying in the abstract (Fox, Elder, Gater, & Johnson, 2010), we hypothesized that strong global BJW beliefs would instead predict more tolerance and less condemnation when participants were presented with specific behaviors that could be construed as bullying. In two vignette-based experiments, global BJW (but not personal BJW), predicted less negative reactions to bullying, and did so regardless of whether the behavior was explicitly labeled as being a case of bullying. Implications of these results are discussed.